LOX-1: Regulation, Signaling and Its Role in Atherosclerosis - Ajoe John Kattoor; Akshay Goel; Jawahar L. Mehta (Antioxidants, 2019)
Atherosclerosis has long been known to be a chronic inflammatory disease. In addition, there is intense oxidative stress in atherosclerosis resulting from an imbalance between the excess reactive oxygen species (ROS) generation and inadequate anti-oxidant defense forces. The excess of the oxidative forces results in the conversion of low-density lipoproteins (LDL) to oxidized LDL (ox-LDL), which is highly atherogenic. The sub-endothelial deposition of ox-LDL, formation of foamy macrophages, vascular smooth muscle cell (VSMC) proliferation and migration, and deposition of collagen are central pathophysiologic steps in the formation of atherosclerotic plaque. Ox-LDL exerts its action through several different scavenger receptors, the most important of which is LOX-1 in atherogenesis. LOX-1 is a transmembrane glycoprotein that binds to and internalizes ox-LDL. This interaction results in variable downstream effects based on the cell type. In endothelial cells, there is an increased expression of cellular adhesion molecules, resulting in the increased attachment and migration of inflammatory cells to intima, followed by their differentiation into macrophages. There is also a worsening endothelial dysfunction due to the increased production of vasoconstrictors, increased ROS, and depletion of endothelial nitric oxide (NO). In the macrophages and VSMCs, ox-LDL causes further upregulation of the LOX-1 gene, modulation of calpains, macrophage migration, VSMC proliferation and foam cell formation. Soluble LOX-1 (sLOX-1), a fragment of the main LOX-1 molecule, is being investigated as a diagnostic marker because it has been shown to be present in increased quantities in patients with hypertension, diabetes, metabolic syndrome and coronary artery disease. LOX-1 gene deletion in mice and anti-LOX-1 therapy has been shown to decrease inflammation, oxidative stress and atherosclerosis. LOX-1 deletion also results in damage from ischemia, making LOX-1 a promising target of therapy for atherosclerosis and related disorders. In this article we focus on the different mechanisms for regulation, signaling and the various effects of LOX-1 in contributing to atherosclerosis.